2016
DOI: 10.3390/ijms17081368
|View full text |Cite
|
Sign up to set email alerts
|

Syngonanthus nitens Bong. (Rhul.)-Loaded Nanostructured System for Vulvovaginal Candidiasis Treatment

Abstract: Herbal-loaded drug delivery nanotechnological systems have been extensively studied recently. The antimicrobial activity of medicinal plants has shown better pharmacological action when such plants are loaded into a drug delivery system than when they are not loaded. Syngonanthus nitens Bong. (Rhul.) belongs to the Eriocaulaceae family and presents antiulcerogenic, antioxidant, antibacterial, and antifungal activity. The aim of this study was to evaluate the antifungal activity of Syngonanthus nitens (S. niten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…The results were promising, as they demonstrated that this LCPS was transformed into a lamellar liquid crystalline mesophase upon the addition of 100% artificial vaginal mucus. The extract-loaded LCPS was found to be effective 2 days after the initiation of treatment and was more effective than the extract solution alone (42).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The results were promising, as they demonstrated that this LCPS was transformed into a lamellar liquid crystalline mesophase upon the addition of 100% artificial vaginal mucus. The extract-loaded LCPS was found to be effective 2 days after the initiation of treatment and was more effective than the extract solution alone (42).…”
Section: Resultsmentioning
confidence: 92%
“…Dos Santos Ramos et al (42) have developed an LCPS composed of 40% oleic acid, 40% PPG-5-CETETH-20, and 20% polymer dispersion for the incorporation of an extract of the medicinal plant Syngonanthus nitens Bong (Rhul.) This LCPS was examined pre-clinically for the treatment of vulvovaginal candidiasis using an in vivo study conducted in Wistar rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, the administration of estradiol is necessary to induce a state of pseudo‐estrus, which transforms the columnar epithelium into squamous epithelium, increases the glycogen content, decreases the pH, and increases substrates that are conducive to the establishment of infection by C. albicans , in addition to inhibiting immune defenses . Furthermore, the immunosuppressant cyclophosphamide can inhibit the cellular and humoral immune responses, a condition necessary for the successful establishment of infection, and the inclusion of a wide‐spectrum antibiotic also favours infection by yeast, due to the reduction in the bacterial microbiota . After the infection establishment, treatment with cream containing curcumin was able to gradually reduce the fungal load over the days of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…GG stem flavonoids were described as being composed by three flavanones and five flavones (Pacifico et al, ). Nowadays, the extract of S. nitens stems has been studied as a natural product against different Candida species and clinical isolates from patients with vulvovaginal candidiasis (VVC), which results demonstrated that the antifungal properties are effective and it has the ability to inhibit the fungal‐host invasion on human cells (de Freitas Araújo et al, ; dos Santos Ramos et al, ). Recently, a work suggested that the study of crude extracts can provide explanations about the compounds behaviors and it shows the importance of possible bioinspired applications of a complete scientific understanding of S. nitens (Berlim et al, ).…”
Section: Introductionmentioning
confidence: 99%